2017
DOI: 10.1002/ange.201701547
|View full text |Cite
|
Sign up to set email alerts
|

A Cascade of Redox Reactions Generates Complexity in the Biosynthesis of the Protein Phosphatase‐2 Inhibitor Rubratoxin A

Abstract: Redox modifications are key complexity‐generating steps in the biosynthesis of natural products. The unique structure of rubratoxin A (1), many of which arise through redox modifications, make it a nanomolar inhibitor of protein phosphatase 2A (PP2A). We identified the biosynthetic pathway of 1 and completely mapped the enzymatic sequence of redox reactions starting from the nonadride 5. Six redox enzymes are involved, including four α‐ketoglutarate‐ and iron(II)‐dependent dioxygenases that hydroxylate four sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In the biosynthesis of cornexistin, the involvement of similar proteins was also suggested by a gene knockout . Considering that similar genes were conserved in the gene cluster for 2 and rubratoxin A, it is likely that they are generally involved in the dimerization, although the mechanism of dimerization still remains to be fully understood. In addition, the construction of the 8-membered ring found in 3 has not been investigated to date.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the biosynthesis of cornexistin, the involvement of similar proteins was also suggested by a gene knockout . Considering that similar genes were conserved in the gene cluster for 2 and rubratoxin A, it is likely that they are generally involved in the dimerization, although the mechanism of dimerization still remains to be fully understood. In addition, the construction of the 8-membered ring found in 3 has not been investigated to date.…”
mentioning
confidence: 99%
“…In addition, genes encoding a KI-like protein (ZopC) and PEBP homologue (ZopN), both of which are involved in the dimerization, are also found. To note, ZopK was initially annotated as a hypothetical protein, while a secondary structure search using phyre2 indicated weak homology to α-ketoglutarate-dependent dioxygenase (α-KGDO), which is often involved in modification of nonadrides. , …”
mentioning
confidence: 99%
“…Oikawa also reported a similar early pathway towards the phomoidrides 8 and Tang and coworkers have shown that the biosynthesis of rubratoxins follows the same pathway. 9 Construction of the carbocyclic ring appears to be catalysed by pairs of enzymes with homology to phosphatidylethanolamine binding proteins (PEBP) and ketosteroid isomerase-like enzymes (KI).…”
mentioning
confidence: 99%
“…61 This revealed a BGC containing the expected PKS, CS, 2MCDH, KI and PEBP genes, as well as genes encoding seven further redox enzymes. Knockout experiments supported by re-feeding, and in vitro assays of isolated recombinant enzymes elucidated the oxidative steps, and also implicated an interesting possibility of an early hydroxylation of one maleic anhydride precursor 60 and an asymmetric dimerisation to form the initial nonadride 61 (Scheme 6B).…”
mentioning
confidence: 99%